2019
DOI: 10.1177/2309499018822221
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome after the nonsurgical treatment for adolescent spasmodic valgus foot

Abstract: Background: Adolescent spasmodic valgus foot is usually associated with resistant pain and deformity. It shows controversy regarding its incidence, etiology, and treatment. Our study aimed to evaluate the functional outcome after the nonsurgical treatment for such condition. Methods: This study included 50 planovalgus feet secondary to peroneal or peroneo-extensor spasm in 33 adolescents with a mean age of 14 + 2.8 years. The procedure included foot manipulation under general anesthesia, sinus tarsi injection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Todd, in 1939 [ 31 ], reported that 5.7% of individuals with FFD had the unique entity of SFFD; he reported that those were adolescent patients who were involved in laborious work requiring standing for long periods; furthermore, he mentioned that in most of the unilateral cases, a history of foot and ankle trauma was detected, and in bilateral cases, the severity was not equal. Rizk and Kandil [ 17 ] and Blockey [ 13 ] reported that their patients started complaining at 12 to 14 years old after being involved in strenuous activities or having repeated traumas. Furthermore, Pauk and Ezerskiy cautioned about being overweight combined with an increase in physical activities as risk factors for FFD complication progression [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Todd, in 1939 [ 31 ], reported that 5.7% of individuals with FFD had the unique entity of SFFD; he reported that those were adolescent patients who were involved in laborious work requiring standing for long periods; furthermore, he mentioned that in most of the unilateral cases, a history of foot and ankle trauma was detected, and in bilateral cases, the severity was not equal. Rizk and Kandil [ 17 ] and Blockey [ 13 ] reported that their patients started complaining at 12 to 14 years old after being involved in strenuous activities or having repeated traumas. Furthermore, Pauk and Ezerskiy cautioned about being overweight combined with an increase in physical activities as risk factors for FFD complication progression [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of SFFD aetiology, a management plan should be initiated if this condition becomes symptomatic, starting with conservative lines such as physiotherapy, serial casting, and local injections, up to surgical correction in refractory cases [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations